Ефективність зберігання плодів груші з використанням антиоксидантів - Гапріндашвілі, Нона Арчилівна; Гаприндашвили, Нона Арчиловна; Gaprindashvili, Nona; Кюрчева, Людмила Миколаївна; Кюрчева, Людмила Николаевна; Kiurcheva, Liudmyla; Войцехівський, В. І.; Войцеховский, В. И.; Voytsekhivskyy, V. (My University, 2012)
En: Established that the processing of fruits pear antioxidant preparations to longterm storage provides increased profitability at average of 28-35%.
Efficiency of fruit storage pears with using of antioxidants
Keywords: плоди груші; антиоксиданти; рентабельність; прибуток; fruits pears; antioxidants; level of profitability; income